Studi Komparatif Pengaruh Problem Based Learning Dan Discovery Learning Terhadap Efikasi Diri Serta Internalisasi Nilai Akhlak Siswa Madrasah Tsanawiyah - Elmira Salsabila; Muhlisin; Rahmi Anekasari (Oasis : Jurnal Ilmiah Kajian Islam, 2026)
Islamic Religious Education at the Madrasah Tsanawiyah (MTS) level plays a significant role in developing students’ self-efficacy and the internalization of moral values. However, learning practices that remain predominantly teacher-centered tend to result in moral values being understood merely at a theoretical level without being fully internalized into students’ daily behavior. This study aims to: (1) analyze the effect of Problem-Based Learning (PBL) on students’ self-efficacy and the internalization of moral values in MTS; (2) analyze the effect of Discovery Learning (DL) on students’ self-efficacy and the internalization of moral values in MTS; and (3) compare the effectiveness of these two learning models. This research employs a qualitative method with a library research approach. Data collection techniques were conducted through the review of various scholarly sources, including books, national and international journal articles, and relevant studies related to PBL, DL, self-efficacy, and the internalization of moral values. Data analysis was carried out using content analysis through the stages of literature selection, thematic categorization, comparative analysis, and data synthesis. The findings indicate that both Problem-Based Learning and Discovery Learning have a positive influence on students’ self-efficacy. Based on the findings of this study, it can be concluded that Problem-Based Learning is a more effective and comprehensive instructional model for Islamic Religious Education in MTS, as it is capable of enhancing students’ self-efficacy while simultaneously optimizing the internalization of moral values. Keywords:  Discovery Learning; Self-Efficacy; Internalization of Moral Values; Madrasah Tsanawiyah; Problem-Based Learning